Spontaneous Fertility after Myomectomy for Pregnancy Desire in Reference University Maternities of Benin from 2016 to 2020: Contributing Factors and Pregnancies Outcome - TOGNIFODE, Mèdessè Véronique; DANGBEMEY, Djima Patrice; DANGBEMEY, D. Patrice; AZONBAKIN, AZANDÉGBÉ SIMON; HOUNKPATIN, BENJAMIN IGNACE B.; DENAKPO, Justin Lewis (My University, 2022)
Introduction: Spontaneous fertility after myomectomy for pregnancy desire remains a concern. Objective : Appreciate spontaneous fertility after a myomectomy for pregnancy desire. Methods: This was a descriptive and analytical study to collect retrospective data on cases of myomectomy pregnancy desire realised between 2016 and 2020 in the university maternity wards of Cotonou. All myomectomy records for desire for pregnancy were identified. The post myomectomie fertility related data and the clinical characteristics influencing the occurrence of pregnancy and its outcome after myomectomy were analyzed with regard to the rules of professional conduct and ethics. Results: On 188 myomectomies performed for desire of pregnancy, 102 had been analyzed. The mean age was 34 years ± 5.7. Nulligest and nulliparous were the most numerous in the respective proportions of 39.2% and 71.6%, and 16.7% (n=17) had a history of polymyomectomy. Fertility after myomectomy was observed in 16.7% (n=17) of cases.The mean time to return to fertility (pregnancy) after myomectomy was 27 months.Alcohol addiction (p=0.00), gestality (p=0.01), myoma size (p=0.00) and adenomyosis (p=0.00) had an negative impact on the time to onset pregnancy after myomectomy. Of 17 pregnancies recorded after myomectomy, 11 (64.7%) progressed normally with term delivery and 5 spontaneous abortions (29.4%) were recorded. One (1) pregnancy was ongoing at the time of the survey. Planned caesarean section (n=9) was the most frequent mode of delivery. Eleven (11) newborns were welcomed and the diaper suites were simple. Conclusion: Spontaneous fertility after myomectomy remains low in our series. Factors with a negative impact on fertility must be taken into account.
Keywords: Myomas; Myomectomies; Fertility; Pregnancy; Cotonou.